Power control for interference avoidance in femtocell network - Al-Hmoudi, Mutieb; Saeed, Rashid Abdelhaleem; Hassan Abdalla Hashim, Aisha; O-Khalifa, Othman; Mahmoud, Omer (INSI Publications, 2011)
Femtocell network is a new technology that uses the advantage of an Internet backbone to enhance the cellular coverage in residential or small business areas. However, due to the expected random deployment of the femtocell access point (FAPs), there is a strong probability of interference among the femtocell nodes and between the femtocells and the macrocell nodes. In this paper, an interference enhancement is developed and designed for two tiers macro-femtocell networks. An adaptive power control is calculated based on selecting the minimum interference channel with the optimized channel gain. In the simulation a number of the FAPs, the distance between the macrocell and the femtocell and the path loss between the macrocell node and the FAPs are used as design parameters. The results show a performance enhancement in the interference degradation ratio (DR).